Cortical pattern of reduced perfusion in hearing loss revealed by ASL‐MRI. Issue 8 (4th February 2019) - Ponticorvo, Sara; Manara, Renzo; Pfeuffer, Josef; Cappiello, Arianna; Cuoco, Sofia; Pellecchia, Maria Teresa; Saponiero, Renato; Troisi, Donato; Cassandro, Claudia; John, Marta; Scarpa, Alfonso; Cassandro, Ettore; et al.
Abstract: Age‐related hearing loss (HL) can be related to brain dysfunction or structural damage and may result in cerebral metabolic/perfusion abnormalities. Arterial spin labeling (ASL) magnetic resonance imaging (MRI) allows investigating noninvasively brain perfusion changes. Pseudocontinuous ASL and T1‐weighted MRI (at 3 T) and neuropsychological testing (Montreal Cognitive Assessment) were performed in 31 HL (age range = 47–77 years, mean age ±  SD = 63.4 ± 8.4 years, pure‐tone average [PTA] HL > 50 dB) and 28 normal hearing (NH; age range = 48–78 years, mean age ±  SD  = 59.7 ± 7.4 years) subjects. Cerebral blood flow (CBF) and gray matter volume (GMV) were analyzed in the cortical volume to assess perfusion and structural group differences. Two HL subjects showing cognitive impairment were excluded from group comparisons. No significant differences in either global or local atrophy were detected between groups but the HL group exhibited significant regional effects of reduced perfusion within the bilateral primary auditory cortex, with maximal CBF difference (−17.2%) in the right lateral Heschl's gyrus. For the whole sample of HL and NH subjects ( n  = 59 = 31 HL + 28 NH), the regional CBF was correlated positively to the regional GMV ( p  = 0.020). In HL subjects ( n  = 31), the regional CBF was correlated negatively to the audiogram steepness (frequency range: 2–4 kHz, right ear: p  = 0.022, left ear: p  = 0.015). The observed cortical pattern of perfusion reduction suggests that neuronal metabolism can be related to HL before the recognition of brain structural damage. This also illustrates the potential of ASL‐MRI to contribute early functional markers of reduced central processing associated with HL.